Using Post-Structuralism to Rethink Risk and Resilience: Recommendations for Social Work Education, Practice, and Research. Issue 2 (4th February 2019) - Prowell, Ashley Nicole
Abstract: Since the 1970s, the construct of resilience has become detached from its original context of trauma and reassembled as a normative behavior, patterned after society's dominant class. A decade after becoming a focus of academic attention, resilience began to influence the advocacy community through the strengths-based approach commonly used by social workers. While many continue to use resilience within the context of trauma, mainstream society has marketed a new construct of resilience with dangerous, underlying assumptions. This conceptual article uses post-structuralism to problematize the construct of resilience within social work and provides suggestions on how to more cautiously and comprehensively implement resilience in social work education, practice, and research. This theoretical application of post-structuralism in social work is important in that it urges social workers to be more critical and to better advocate for marginalized groups through practices and methodologies. This work provides direction for future research, methodological and theoretical positioning for researchers, and guidance for skill building in social work education.